Energy study for the rehabilitation of the old Abbey of Salas de Bureba (Burgos) for residential use. Case study - Raul Briones-Llorente; Juan Maria Hidalgo-Betanzos; Paula Montoya-Saiz; Imanol Ruiz-de-Vergara-Ruiz-de-Azúa; Gabriel Rubio-Pérez; Natalia Muñoz-Rujas; Fernando Aguilar-Romero (Anales de Edificación)
The renovation of buildings is key to the fight against climate change and offers opportunities to fix the population in rural areas, revalue their heritage and help decongest cities. In addition, it has a lower environmental impact than new construction. With this contribution, the energy study for the rehabilitation of the old Abbey of Salas de Bureba, located in the Caderechas Valley, north of Burgos, is presented. The aim is to return the building to its original state, so most of the facades will not be able to be insulated. A detailed energy simulation has been conducted and all viable options have been analysed, applying passive improvements combined with the installation of renewable energies. This project, whose implementation has already begun, has obtained a double A energy rating, which has allowed it to apply for aid from the PREE 5000 Programme.